HEMORRHAGE EXPRESS-DIAGNOSTICS AND THERAPY IN CHILDREN 0-6 MONTHS OF AGE - P. V. Svirin; L. E. Larina (Union of pediatricians of Russia, 2013)
Hemorrhagic conditions are associated with severe health problems and an increase in mortality rate among children. Quick and adequate reaction of a doctor who was the first to appear beside such a patient is necessary to save the child's life; mistakes may lead to severe complications, including fatal outcome. The article formulates methodological recommendations on diagnosing and rendering help to children of the first months of age with developing hemorrhagic manifestations in the environment of neonatal and newborn centers taking into account their laboratorial and therapeutic capabilities.